2018
DOI: 10.1002/acp.3486
|View full text |Cite
|
Sign up to set email alerts
|

Reception and willingness to share pseudo‐profound bullshit and their relation to other epistemically suspect beliefs and cognitive ability in Slovakia and Romania

Abstract: Summary Propensity to judge randomly generated, syntactically correct (i.e., bullshit) statements as profound is associated with a variety of conceptually relevant variables (e.g., intuitive cognitive style and supernatural beliefs). Besides generalizing these findings to a different cultural setting, we examined the relationships to sharing the bullshit on social media. Rating nonsense as profound was associated with a lower cognitive ability; a stronger belief in the paranormal, alternative medicine, and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 33 publications
3
51
0
Order By: Relevance
“…In their seminal work, Pennycook et al (2015) measured bullshit receptivity and found that openness to pseudo-profound bullshit is associated with paranormal, conspiracist, and religious beliefs, as well as with lower intelligence, lower analytical, and higher intuitive thinking style. These findings were replicated and extended using different samples (Čavojová, Secar a, Jurkovič, & Šrol, 2018;Hart & Graether, 2018). Furthermore, all these associations could be explained by the Openness/Intellect simplex model in which pseudo-profound bullshit is negatively related to the constructs of one extreme of the modelintelligence-while positively related to the constructs on the opposite (e.g., apophenia; Bainbridge, Quinlan, Mar, & Smillie, 2019).…”
Section: Pseudo-profound Bullshitmentioning
confidence: 70%
“…In their seminal work, Pennycook et al (2015) measured bullshit receptivity and found that openness to pseudo-profound bullshit is associated with paranormal, conspiracist, and religious beliefs, as well as with lower intelligence, lower analytical, and higher intuitive thinking style. These findings were replicated and extended using different samples (Čavojová, Secar a, Jurkovič, & Šrol, 2018;Hart & Graether, 2018). Furthermore, all these associations could be explained by the Openness/Intellect simplex model in which pseudo-profound bullshit is negatively related to the constructs of one extreme of the modelintelligence-while positively related to the constructs on the opposite (e.g., apophenia; Bainbridge, Quinlan, Mar, & Smillie, 2019).…”
Section: Pseudo-profound Bullshitmentioning
confidence: 70%
“…Experiment 2 tests H1 with novel materials: pseudo-profound bullshit. Previous studies found that pseudo-profound bullshit receptivity was mediated by personality traits, notably lower analytical thinking (Bainbridge et al, 2019;Čavojová et al, 2019;Pennycook et al, 2015). However, to the best of our knowledge, the relationship between communion and pseudo-profound bullshit receptivity has not been studied.…”
Section: Methodsmentioning
confidence: 95%
“…Relying more on one's intuitions instead of engaging in analytical thinking has been associated with a higher likelihood of holding a variety of epistemically suspect beliefs, of sharing fake news, and of finding pseudo-profound bullshit profound (Čavojová et al, 2019;Pennycook & Rand, 2018;Šrol, 2020) . Within this framework, people come to hold epistemically suspect beliefs because they are unable or unwilling to use analytical thinking abilities (Lantian et al, 2020).…”
Section: Individual Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such epistemically suspect beliefs 1 (ESB; Pennycook, Cheyne, Barr, Koehler, & Fugelsang, 2015;Pennycook, Fugelsang, & Koehler, 2015a) comprise a wide category which encompasses beliefs in paranormal phenomena, conspiracy theories, and pseudoscientific claims. Importantly, these beliefs are surprisingly prevalent (e.g., Jensen, 2013;Mancosu, Vassallo, & Vezzoni, 2017), and have been linked to important real-life outcomes such as negative attitudes toward vaccination (Browne, Thomson, Rockloff, & Pennycook, 2015), political extremism (van Prooijen, Krouwel, & Pollet, 2015), rejection of scientific findings , and the tendency to perceive nonsensical bullshit statements as profound and even share them on social media (Čavojová, Secară, Jurkovič, & Šrol, 2019;Pennycook, Cheyne, et al, 2015). For these reasons, it is a matter of great importance to understand the links between miscellaneous types of epistemically suspect beliefs, to uncover their individual difference predictors, and to examine their relationships with related cognitive phenomena, such as the systematic reasoning and decision-making errors studied under the heuristics and biases research tradition Stanovich, West, & Toplak, 2016).…”
Section: Introductionmentioning
confidence: 99%